ZrgA contributes to zinc acquisition in Vibrio parahaemolyticus. Issue 1 (31st December 2023) - Zheng, Chengkun; Qiu, Jun; Zhai, Yimeng; Wei, Man; Zhou, Xiaohui; Jiao, Xinan
ABSTRACT: Metals are nutrients essential for almost all lifeforms. Bacteria have evolved several mechanisms to overcome the metal restrictions imposed by the host. Vibrio parahaemolyticus causes severe threats to public health and significant economic losses in shrimp aquaculture. Herein, we report that ZrgA contributes to zinc acquisition in this pathogen. The operon VP_RS01455 to VP_RS01475 of V. parahaemolyticus encodes the putative Zn transporter ZrgABCDE, whose homologs are widely distributed in Vibrionaceae . RNA sequencing analysis revealed that V. parahaemolyticus modulates the transcriptome in response to Zn limitation. Genes in the Zinc uptake regulator (Zur) regulon are upregulated during Zn limitation, including three genes annotated to encode Zn-binding proteins. Significant upregulation of these three genes during Zn limitation was also confirmed by quantitative real-time PCR (qRT-PCR) analysis. However, only the mutants containing a VP_RS01470 ( zrgA ) deletion exhibited impaired growth under Zn-deficient conditions, indicating that VP_RS01470 plays the predominant role in V. parahaemolyticus Zn acquisition. The VP_RS01470 deletion mutant displayed a false appearance of decreased swimming motility under Zn-deficient conditions, as revealed by the fact that the polar flagellar-related genes were not downregulated in the mutant. Moreover, VP_RS01470 deletion produced no noticeable impact on the swarming motility and virulence in mice. qRT-PCR analysis and β-galactosidase activity assays indicated that Zur negatively regulates VP_RS01470 expression in V. parahaemolyticus . Collectively, our findings suggest that ZrgA is required for Zn acquisition in V. parahaemolyticus and highlight the importance of detecting the expression of flagellar genes during analysis of motility of a mutant deficient in growth.